A Study on the Construction of a Linked Database for an Integrated Service Platform of Local Culture and Arts Resources - Noh, Younghee; kwak, woojung (International Journal of Knowledge Content Development & Technology, 2023)
In this study, it was intended to explore a way to build a DB which links the resources and areas and regions already registered as cultural assets in connection with a project which is newly building local culture and arts resources. Towards this end, this study first identified the type and scale of existing local culture and arts resources that could be linked. Following which, to link the local cultural resources and collected cultural assets, this study investigated the websites such as the Cultural Heritage Administration’s National Cultural Heritage Portal, municipal and provincial tangible cultural festivals, municipal and provincial intangible cultural assets, and Gyeonggi Memory. Furthermore, this study identified the amount of information sources to be built and the current status of each information source to identify detailed information sources. Finally, the metadata of local culture and arts resources were presented by classifying them into material and publication data metadata, document metadata, audiovisual metadata, oral recording metadata, village information metadata, and personal information village information metadata.